Ocena ryzyka wystąpienia Phytophthora ramorum w lasach Polski - Malinowska, Ewelina; Oszako, Tomasz; Łukaszewicz, Jan (Leśne Prace Badawcze, 2025)
The primary aim of this study was to analyze the risk of introducing the pathogen Phytophthora ramorum to Poland via seedlings (e.g., from ornamental nurseries) into forests, and the associated consequences for Polish forest-forming species. The methodology was based on a Pest Risk Assessment (PRA) performed according to EFSA (European Food Safety Authority) guidelines. The theoretical foundation involved a review of the relevant literature, including the characteristics, detection possibilities, and disease symptoms caused by P. ramorum in various hosts. The PRA specifically assessed the pathogen’s biology, ecology, and current global spread and current global distribution/dispersal patterns. The analysis then focused on the factors critical for its potential establishment in Polish forest ecosystems, such as climatic conditions, the presence of potential hosts in Poland, and possible transmission routes (especially via nursery stock from affected countries). Our studies have shown a risk of transmission and establishment of P. ramorum in Polish forests. This finding is driven by the global commercial movement of plant material combined with the availability of potential hosts. Although Poland’s climate is cold and temperate, which generally does not favour the pathogen’s widespread development, P. ramorum could survive and establish in specific, more favourable regions, e.g., in the south-western part of the country. This presents serious potential consequences for the health of tree populations, forest ecosystems, and the forestry sector.